Medical treatment for myasthenia gravis at a Myasthenia Center - Tatyana Valentinovna Romanova (Неврология, нейропсихиатрия, психосоматика, 2013)
The paper analyzes the results of treatment in 373 patients included in the Samara Region’s register of myasthenia gravis. The average disease duration was 9.7±7.6 years. Treatment encompassed symptom control with acetylcholinesterase inhibitors and immunosuppressive therapy. To achieve remission and good compensation, most cases needed the combined use of anticholinesterase inhibitors and immunosuppression with glucocorticoids and/or cytostatics. The efficiency of glucocorticoid and cytostatic therapies did not differ essentially. The adverse reactions of the treatment were evaluated. Therapy could achieve stabilization and improvement in 88.2% of cases.